Về một mô hình dự báo trong kế hoạch hóa việc huy động và hoàn vốn đầu tư - Hỷ, Nguyễn Quý; Lam, Lê Xuân (Journal of Computer Science and Cybernetics, 2016)
In this work, we construct a recurrent equation for the number of capital invested in process of production, of which product can be used to reimburse capital of investment. The values of this reimbursement by cash and product are evaluated in the work as a function of solution of the recurrent equation.